Evaluation of a microhaplotypes panel for forensic genetics using massive parallel sequencing technology. (July 2019) - Turchi, Chiara; Melchionda, Filomena; Pesaresi, Mauro; Tagliabracci, Adriano
Highlights: 89 Microhaplotypes were selected and evaluated using an MPS assay. Based on MPS data, the panel was reduced to 87 loci, comprised of 266 SNPs. Genotype and haplotype frequencies and effective number of alleles was estimated. 32 Microhaps display Ae values > 3.0 and the matching probability was 1.6 × 10 −33 . The results of this study confirm the utility of microhaps in forensic genetics. Abstract: Massive parallel DNA sequencing (MPS) makes it possible to explore a new type of genetic marker, known as microhaplotypes or microhaps. These loci were recently introduced in the landscape of forensic genetic and appear to be useful for identification purposes, reconstruction of family relationships, ancestry prediction and DNA mixtures deconvolution. Microhaplotypes loci, based on 89 loci in ALFRED, were selected and their genetic variations in 100 Italian individuals were evaluated by using MPS, in order to make inference about utility of a set of microhaps in forensic genetics. After MPS, the panel was reduced to 87 microhaps, comprised of 266 different SNPs and spread across 22 human autosomes. Genotype and haplotype frequencies were estimated, as well as the effective number of alleles at each locus (Ae ), which relates to the usefulness of the locus in resolution of relationships and deconvolution of DNA mixtures. Overall, the Ae values for the 87 microhaps range from 1.010 to 8.344, with about 80% showing values greater than 2.0. Noteworthy, 32 microhaps display Ae values greater than 3.0 and 18 loci Ae above 4.0. To explore the suitability of microhaplotypes in mixture deconvolution, the probability of detecting a mixture, as a function of Ae, was inferred for different groups of loci. Considering the fourteen loci with Ae between 3.0 and 3.999 the probability of detecting a mixture was at least 0.99973, while considering the ten loci with Ae between 4.0 and 4.999 the probability was at least 0.99998. Moreover, when considering just the six loci with Ae between 5.0 and 5.999 the probability of detecting a mixture was at least 0.99984, while when considering just the two loci with Ae above 6 the probability was 0.97228. Combining these 32 MH loci, the theoretical probability of detecting a mixture was 0.999999999999973. These results make the subset of 32 loci with Ae above three informative for mixture resolution. The individual matching probabilities (PI) of the 87 microhaps ranged from 0.032 to 0.9802. Considering the 32 microhap loci with Ae greater than 3.0, the cumulative PI value was 1.6 × 10 −33, while considering the 18 microhap loci with Ae above 4.0, the cumulative PI value was 2.34 × 10 -21 . Overall the results of this study confirmed the utility of microhaps in forensic genetics.